Relationship of Family Social Support with Marital Readiness in Women in Early Adult Stage - Fitriani Syamal; Taufik Taufik (Jurnal Neo Konseling, 2019)
The readiness of a person in living a married life is one of the important things to form a happy family. The level of readiness of an individual to get married is influenced by several factors, one of the factors that plays an important role is social support. The problem to be examined in this study is to find a relationship between family social support and marriage readiness.This type of research is a quantitative descriptive correlational method with a descriptive correlational method to find the relationship between family social support and marriage readiness. This research was conducted in the East PariamanSubdistrict of Pariaman City with the number of research subjects were 30 early adult women who were about to get married. The instrument used in this study was a questionnaire.The results showed that the family's social support was in the very high category and the readiness to get married in the early adult women was also in the very high category. Based on the results of the data that has been processed there is a significant relationship with a positive direction between family social support and marriage readiness. It can be concluded that family social support has a positive impact on marriage readiness in early adult women in Pariaman sub-district, Pariaman City.